“WAYS FOR TERTIARY LEVEL STUDENTS IN BUILDING ENGLISH SPEAKING PERFORMANCE” - Fika Megawati; Vidya Mandarani (Script Journal: Journal of Linguistics and English Teaching, 2017)
Abstract: This study aims to find out the strategies used by tertiary level students in performing English communication. This research was a descriptive study involving English Education Study Program students. Data analysis included in-depth transcribing on the students’ speaking performance and the result of interview. The findings show that the communication strategies used in the conversation consisted of avoidance, paraphrase, borrowing, appeal for assistance, and mime. The common strategy lied on mime, while avoidance and paraphrase strategies were not frequently applied. The results show communication strategies were effective in helping the first language students in learning English as their foreign language. Communication strategies give solution to cope with difficulties in learning English. Communication strategies are highly suggested to be socialized to EFL learners as an alternative way to improve speaking performance.